STUDENTS’ PERCEPTION ON VIRTUAL GROUP OF E-LEARNING IN THE MIDDLE OF PANDEMIC COVID -19 - Said, Ratna (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
The research aims to describe students’ perception on virtual group of e-learning in the middle of pandemic Covid-19. This research is a descriptive study with two types of research methods, namely library research and Google form questionnaire survey research. Result of the research shown that there was a positive perception of virtual group members through confidence 35, 7%, collaboration 60, 7%, accountability 57, 1 % and encounter obstacle in virtual group 60, 7 %.